ESTUDO DE RESÃDUO ORGÃ‚NICO DA PRODUÃ‡ÃƒO DE ANTIBIÃ“TICO (TETRACICLINA) COMO BIOFERTILIZANTE: TESTE EM ALFACE (ð˜“ð˜¢ð˜¤ð˜µð˜¶ð˜¤ð˜¢ ð˜´ð˜¢ð˜µð˜ªð˜·ð˜¢ L.) - Canales, JerÃ´nimo Ismael; BÃ¼ll, Leonardo Theodoro (REVISTA DE AGRICULTURA, 2020)
ESTUDO DE RESÃDUO ORGÃ‚NICO DA PRODUÃ‡ÃƒO DE ANTIBIÃ“TICO (TETRACICLINA) COMO BIOFERTILIZANTE: TESTE EM ALFACE (ð˜“ð˜¢ð˜¤ð˜µð˜¶ð˜¤ð˜¢ ð˜´ð˜¢ð˜µð˜ªð˜·ð˜¢ L.)